2021
DOI: 10.1093/scan/nsab062
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific interaction between cortisol and striato-limbic responses to psychosocial stress

Abstract: Although women and men differ in psychological and endocrine stress responses as well as prevalence rates of stress-related disorders, knowledge on sex differences regarding stress regulation in the brain is scarce. Therefore, we performed an in-depth analysis of data from 67 healthy participants (31 women, taking oral contraceptives), who were exposed to the ScanSTRESS paradigm in an fMRI study. Changes in cortisol, affect, heart rate, and neural activation in response to psychosocial stress we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 94 publications
0
21
1
Order By: Relevance
“…Depending on performing ScanSTRESS PS+ or PS−, cortisol elevations were differently associated with stress-related responses in striatolimbic structures: Higher increases were associated with activations in the ScanSTRESS PS+ group, but with deactivations in the ScanSTRESS PS− group. It is, therefore, tempting to speculate that the present results again suggest that (striato)limbic structures are decisive for the processing of psychosocial stress (Henze et al, 2020(Henze et al, , 2021. In accordance with our investigation of gender effects regarding differences in distinct stress response systems, where we found males and females to exhibit comparable affective and HR outcomes, but to show differences in the underlying neural responses (Henze et al, 2021), our present results demonstrate that merely because a response difference does not manifest psychoendocrinologically or behaviorally, this does not imply that the same is true on the neural level (Cahill, 2006).…”
Section: Neural Responsesmentioning
confidence: 66%
See 3 more Smart Citations
“…Depending on performing ScanSTRESS PS+ or PS−, cortisol elevations were differently associated with stress-related responses in striatolimbic structures: Higher increases were associated with activations in the ScanSTRESS PS+ group, but with deactivations in the ScanSTRESS PS− group. It is, therefore, tempting to speculate that the present results again suggest that (striato)limbic structures are decisive for the processing of psychosocial stress (Henze et al, 2020(Henze et al, , 2021. In accordance with our investigation of gender effects regarding differences in distinct stress response systems, where we found males and females to exhibit comparable affective and HR outcomes, but to show differences in the underlying neural responses (Henze et al, 2021), our present results demonstrate that merely because a response difference does not manifest psychoendocrinologically or behaviorally, this does not imply that the same is true on the neural level (Cahill, 2006).…”
Section: Neural Responsesmentioning
confidence: 66%
“…With regard to the induction of acute psychosocial stress, our group recently developed and refined the neuroimaging stress protocol Scan-STRESS (Henze et al, 2020(Henze et al, , 2021Konzok et al, 2021;Streit et al, 2014), applying the same stresseliciting components as in the well-established TSST (i.e., social-evaluative threat and uncontrollability; Dickerson & Kemeny, 2004). Exposure to ScanSTRESS resulted in significant increases in salivary cortisol levels, heart rate (HR), and negative affect (NA) ratings as well as in (de)activations of distinct (pre)limbic structures (Henze et al, 2020).…”
Section: Public Significance Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Other proximal environmental factors have been documented, supporting the high risk associated with bullying (Holt et al, 2015;O'Reilly et al, 2021;Tang et al, 2020;Zaborskis, Ilionsky, Tesler, & Heinz, 2019), alcohol, and drug use (Mars et al, 2019a;Sher & Zalsman, 2005). Consistent with sex differences in stress reactivity (Henze et al, 2021;Liu & Zhang, 2020), prior evidence suggested that negative life events may differentially affect adolescent boys and girls (Coelho et al, 2018) and lead to different responses (Bordin, Handegard, Paula, Duarte, & Ronning, 2022;Tang et al, 2020). However, this needs further exploration in the context of STB.…”
Section: Introductionmentioning
confidence: 86%